Feasibility Study of a Digital Platform for sharing household equipment and resources for a fee in Gauteng - Nkomo, Greaterman (University of the Witwatersrand, Johannesburg, 2021)
This research seeks to investigate the feasibility of a digital sharing application that connects the supply and demand for everyday household components. The research methodology that was used in this study was the qualitative methodology, using interviews. Twelve interviews were conducted via video conferencing using Zoom and Microsoft Teams and all the participants were from the Johannesburg region in Gauteng. The research findings were that the participants had some assets that were not being utilized and they are willing to list them in a sharing application to make extra income. The research revealed that the key motivation for utilizing the digital sharing application is the economic benefits associated with participating, either through saving money by renting the tools instead of purchasing every tool that they may need to complete a project or to make extra money by sharing their tools for a fee or to save money. The research shows that people are open to utilizing digital sharing applications if the application meets certain standards such as having up to date information; secure and easy to use. The household equipment that people are willing to share include garden tools; toolbox kits; laundry equipment; outdoor furniture; picnic tables and many more. Based on this research, there is a market for a digital sharing application that focuses on the everyday household components
A research report presented in partial fulfillment for the degree of Master of Business Administration to the Faculty of Commerce, Law, and Management, University of the Witwatersrand, Johannesburg 2021
Keywords: Sharing economy; Digital Applications; Collaborative Consumption; Technology Adoption; Trust; Benefits; UCTD; SDG-9: Industry, innovation and infrastructure